Macitentan for the treatment of portopulmonary hypertension (PORTICO): a multicentre, randomised, double-blind, placebo-controlled, phase 4 trial. Issue 7 (July 2019) - Sitbon, Olivier; Bosch, Jaume; Cottreel, Emmanuelle; Csonka, Denes; de Groote, Pascal; Hoeper, Marius M; Kim, Nick H; Martin, Nicolas; Savale, Laurent; Krowka, Michael
Summary: Background: No dedicated randomised clinical trials have evaluated therapies for pulmonary arterial hypertension in patients with portopulmonary hypertension. The endothelin receptor antagonist macitentan has demonstrated long-term efficacy in pulmonary arterial hypertension with a good hepatic safety profile. We aimed to evaluate efficacy and safety of macitentan in patients with portopulmonary hypertension. Methods: PORTICO was a phase 4 study done in 36 centres in seven countries, consisting of a 12-week double-blind period (randomly assigned 1:1 to macitentan 10 mg or placebo once daily) followed by a 12-week open-label period. Adults (≥18 years) with portopulmonary hypertension, a 6-minute walk distance of 50 m or more, and with pulmonary vascular resistance of 320 dyn·s·cm −5 or more without severe hepatic impairment (Child-Pugh class C or model for end-stage liver disease score ≥19) were eligible. The primary endpoint was pulmonary vascular resistance at week 12, expressed as ratio of baseline in the full analysis set. Safety was assessed throughout. This trial is registered atClinicalTrials.gov, numberNCT02382016 . Findings: Between June 23, 2015, and July 28, 2017, 85 patients were randomly assigned to macitentan (n=43) or placebo (n=42). At baseline, 54 (64%) were receiving background therapy for pulmonary arterial hypertension. Most patients were WHO functional class II (50, 59%) or III (33, 39%) with a mean 6-minute walk distance of 384·5 m (SD 103·9). At week 12, the geometric mean ratio of baseline pulmonary vascular resistance was 0·63 (95% CI 0·58–0·67) in the macitentan group and 0·98 (95% CI 0·91–1·05) in the placebo group, corresponding to a ratio of geometric mean for pulmonary vascular resistance of 0·65 (95% CI 0·59–0·72, p<0·0001), which in turn represented a 35% (95% CI 28–41) reduction in pulmonary vascular resistance with macitentan versus placebo. During the double-blind period, 36 (84%) macitentan-treated and 33 (79%) placebo-treated patients had adverse events, and nine (21%) and six (14%), had serious adverse events. Four (9%) macitentan-treated patients had an adverse event leading to discontinuation versus none in the placebo group. The most frequent adverse event during the double-blind period was peripheral oedema (11 [26%] in the macitentan group and five [12%] in the placebo group). Interpretation: Macitentan significantly improved pulmonary vascular resistance in portopulmonary hypertension patients, with no hepatic safety concerns. Funding: Actelion Pharmaceuticals Ltd.